PROFITS ANALYSIS OF POLYCULTURE OF MILKFISH AND DRAGON FRUIT IN SARANG BURUNG VILLAGE JAWAI DISTRICT - Nur Istiqamah; Uray Januardy; Muslimah Muslimah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Food diversification is the effort to increase the availability of diverse foods based on the potential of local resources to support food security and improve community welfare. One way to achieve this is by developing diversified farming and fishing businesses. However, developing just one of these sectors requires more land, and land availability is decreasing in many areas. This is due to the conversion of land for industrial and residential use. As the population grows, the demand for food continues to increase. Additionally, the demand for fish as a source of protein is increasing due to growing public awareness of nutritional needs. Therefore, technological innovations are needed to accommodate these demands, one of which is polyculture. This descriptive study aims to identify the benefits of polyculture between milkfish and dragon fruit cultivation on the same land in Sarang Burung Danau Village Jawai District. The results show that polyculture between milkfish and dragon fruit is beneficial as a means of meeting the community's food needs and as a source of economic income.